Application of Augmented Reality and 3D Animation in School Promotion Media - vania rampo; Brave A. Sugiarso; Rizal Sengkey (Jurnal Teknik Informatika, 2023)
SMK Negeri Pertanian Pembangunan Kalasey, located in Kalasey Satu, Kec. Mandolang, Kab. Minahasa, North Sulawesi Province, currently still uses printed media as a school promotion media. However, there are limitations of printed media in describing the school environment and facilities in detail due to visualization that is limited to text and images, so media that can provide information in a more interactive and detailed manner is needed. Through the advancement of multimedia technology, such as augmented reality and 3D animation, these two technologies can be utilized to complete detailed information that has not been included in school promotional media. The purpose of this research is to produce augmented reality and 3D animation applications that will be used as school promotional media to the public. This research uses the Multimedia Development Life Cycle (MDLC) method which consists of 6 stages and marker based tracking method to detect marker. Based on the results and testing conducted, the conclusion is that augmented reality and 3D animation can be used as a school promotional media in introducing school facilities and infrastructure and to provide a real picture of the school environment that is easy to understand by prospective new students. Key words— 3D Animation; Augmented Reality; Marker Based Tracking; School Promotion Media